Framework of Industry 4.0 Technologies - Oláh, Judit (International Journal of Engineering and Management Sciences, 2019)
The increasing competition and globalization have changed the micro- and macro environment of companies worldwide. The number 4.0 marks the fourth industrial revolution, bringing information technology and automation closer together leading to fundamental changes in production methods. It is not only about the penetration of technology but also about the paradigm shift in business processes. Industry 4.0 is becoming a daily reality for domestic companies as well, giving rise to the era of high-level interaction among production resources and different players. Industry 4.0 will transform the structure of production and change global competitiveness giving enterprises new opportunities to create added value. In my study I presented the concept of Industry 4.0, its framework and innovative technologies. I described the intelligent logistics solutions and the most important advantages of Industry 4.0. Essentially, the use of these tools include in addition to the explosive development of industry the digitalisation of the entire economy affecting society as a whole. It is of great importance that small and medium-sized enterprises also respond to new technological opportunities otherwise will significantly lagging behind in the digital transition.